2005
DOI: 10.2134/jeq2005.0581
|View full text |Cite
|
Sign up to set email alerts
|

Resuspension of Sediment‐Associated Escherichia coli in a Natural Stream

Abstract: In this study, a tracer bacteria was used to investigate the resuspension and persistence of sediment-associated bacteria in a small alluvial stream. The study was conducted in Swan Creek, located within the Grand River watershed of Ontario, Canada. A 1.1-m2 section of the bed was seeded with a strain of Escherichia coli resistant to nalidixic acid (E. coli NAR). The survival, transport, and redistribution of the tracer bacteria within a 1.7-km river section downstream of the source cell was assessed for a 2-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
133
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 210 publications
(139 citation statements)
references
References 24 publications
4
133
1
1
Order By: Relevance
“…Hydrodynamics of the benthic water column simulatorIn many field studies, resuspension was initiated by creating artificial flooding events or by mechanically agitating (raking) bed sediments (Nagels et al 2002;Jamieson et al 2005) and in lab studies by horizontal shaking (Stå hlberg et al 2006;Li and Huang 2010). The applicability of such approaches is questionable since either natural hydrodynamics and/or resuspension-associated concomitant benthic nutrient supply to the bacterial community are not appropriately simulated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Hydrodynamics of the benthic water column simulatorIn many field studies, resuspension was initiated by creating artificial flooding events or by mechanically agitating (raking) bed sediments (Nagels et al 2002;Jamieson et al 2005) and in lab studies by horizontal shaking (Stå hlberg et al 2006;Li and Huang 2010). The applicability of such approaches is questionable since either natural hydrodynamics and/or resuspension-associated concomitant benthic nutrient supply to the bacterial community are not appropriately simulated.…”
Section: Discussionmentioning
confidence: 99%
“…The variable time lags between increase in nutrient availability and bacterial multiplication can explain why none of the regressions were significant. Jamieson et al (2005) reported values for E of colony forming units (CFU) E CFU for an alluvial stream sediment (loss on ignition 5 8% dry wt), Swan Creek, southern Ontario, Canada. During storm events, E CFU varied between 39.6 3 10 6 CFU m 22 h 21 at t b 5 1.7 N m 22 (u* , 4.12 cm s 21 ) and 54 3 10 6 CFU m 22 h 21 at t b 5 1.5 N m 22 (u* , 3.87 cm s 21 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This transport can have a major effect on the quality of bathing waters. Jamieson et al [4] conducted field experiments in Swan Creek, Canada, by using the bacteria tracer E. coli NAR in their studies. They found that the reappearance of the bacteria tracer in the water column coincided with increases in the total suspended solids load, which indicated that the E.coli NAR were being re-suspended with the sediment load.…”
Section: Introductionmentioning
confidence: 99%